Candida tropicalis: insight into the characteristics and outcome of adult patients admitted in medical and surgical intensive care units - Sandhu, Raminder; Aggarwal, Ramnika; Kumar, Surinder; Budhani, Diksha (International Journal of Research in Medical Sciences, 2019)
Background: Non albicans species are emerging increasingly as significant ICU pathogens. The increasing incidence of C. tropicalis infections is a significant problem because of its ability to develop rapid resistance to fluconazole. Methods: The study was designed to isolate, evaluate the risk factors and outcome of C. tropicalis infection from intensive care units. Identification was done by the biochemical methods. A total of 89 patients culture positive for C. tropicalis were selected for retrospective analysis over a period of one year. We collected various data about risk factors and outcome from the medical records. Results: A total of 89 patients culture positive for Candida tropicalis were analysed. Majority of these culture isolates were obtained from their blood (59.55%) followed by urine samples (31.46%). The indwelling devices (93.2%) remained a highest risk followed by prolonged administration of antibiotic therapy (92.1%) and admission in ICU for more than a week (88.8%). Overall mortality rate was 31.5%. Mortality was higher in patients with longer total length of stay in hospital (89.3%; p 1.000), indwelling devices (85.7%; p 0.5663) and in whom the antimicrobial therapy was administered for prolonged duration (82.1%; p 0.7581), although these factors remained statistically insignificant. 92.1% of isolates were sensitive to amphotericin B and showed 52.8%; 9.0% sensitivity to itraconazole and fluconazole respectively. Conclusions: C. tropicalis is now classified as the third or fourth NAC species being commonly isolated from clinical samples and associated with persistent systemic infections leading to a longer stay in the hospital. Several virulence factors seem to be responsible for high dissemination and mortality.